CD4+ T Cells Have a Permissive Effect on Enriched Environment-Induced Hippocampus Synaptic Plasticity - Zarif, Hadi; Hosseiny, Salma; Paquet, Agnès; Lebrigand, Kevin; Arguel, Marie-Jeanne; Cazareth, Julie; Lazzari, Anne; Heurteaux, Catherine; Glaichenhaus, Nicolas; Chabry, Joëlle; Guyon, Alice; Petit-Paitel, Agnès (Frontiers in Synaptic Neuroscience, 2018)
Living in an enriched environment (EE) benefits to health by acting synergistically on various biological systems including the immune and the central nervous systems. The dialogue between the brain and the immune cells has recently gained of interest and is thought to play a pivotal role in beneficial effects of EE. Recent studies show that T lymphocytes have an important role in hippocampal plasticity, learning and memory although the precise mechanisms by which they act on the brain remain elusive. Using a mouse model of EE, we show here that CD4+ T cells are essential for spinogenesis and glutamatergic synaptic function in the CA of the hippocampus. However, CD4+ lymphocytes do not influence EE-induced neurogenesis in the DG of the hippocampus, by contrast to what we previously demonstrated for CD8+ T cells. Importantly, CD4+ T cells located in the choroid plexus have a specific transcriptomic signature as a function of the living environment. Our study highlights the contribution of CD4+ T cells in the brain plasticity and function.